A portable, low-cost relaxed eddy accumulation (REA) system for quantifying ecosystem-level fluxes of volatile organics. (1st December 2020) - Sarkar, Chinmoy; Turnipseed, Andrew; Shertz, Stephen; Karl, Thomas; Potosnak, Mark; Bai, Jianhui; Serça, Dominique; Bonal, Damien; Burban, Benoit; Lopes, Paula R.C.; Vega, Oscar; Guenther, Alex B.
Abstract: Quantification of biogenic volatile organic compound (BVOC) fluxes into the atmosphere is crucial to understand their role in atmospheric oxidation and biogeochemical cycles. BVOC flux measurements were carried out in nine forest ecosystems using a relaxed eddy accumulation (REA) based sampling system, which is easily transportable, simple to operate and designed to be low-cost and therefore can easily be deployed at multiple remote locations. The REA measurements were carried out during daytime between 06:00 and 18:30 (Local Time) with a flux averaging period of 30 min. A detailed description of the REA sampling setup, operational procedure and validation by comparison with full eddy covariance (EC) BVOC flux measurements is provided. BVOC flux measurements from established long-term carbon and water flux tower sites in nine forest ecosystems are compared including Manitou Forest Observatory in Colorado, USA (pine woodland forest), Niwot Ridge AmeriFlux site in Colorado, USA (subalpine forest), Deer Canyon Preserve in New Mexico, USA (pinyon-juniper forest), Lei bamboo forest site near Taihuyuan, China, Qianyanzhou ChinaFLUX site in China (pine forest), Baskett Wildfire Refuge MOFlux site in Missouri, USA (deciduous oak forest), University of Michigan Biological Station PROPHET site in Michigan, USA (mixed deciduous forest), Changbai Mountain Forest Research Station in China (mixed deciduous forest) and the Guyaflux site (GF-Guy) in French Guiana (tropical rainforest). BVOC flux measurements using our REA setup confirm dominance of 2, 3, 2- methylbutenol (2, 3, 2-MBO) at the Manitou Forest Observatory and Niwot Ridge sites in Colorado. Monoterpene fluxes measured by REA showed good agreement (within ±10%) with monoterpene fluxes measured by PTR-MS at the Manitou Forest Observatory. The MOFlux site in Missouri was dominated by isoprene emissions (average flux of 9.5 mg m −2 h −1 ) whereas the Deer Canyon site was dominated by α-pinene emissions (average flux 0.73 mg m −2 h −1 ). Mixed deciduous forest sites at the PROPHET Station in Michigan and Changbai Mountain Forest Research Station in China primarily emitted isoprene along with some α-pinene, β-pinene and d-Limonene. Isoprene and α-pinene were the dominant BVOCs emitted from the subtropical Lei bamboo plantation at the Taihuyuan site in China while the pine forest site at Qianyanzhou in China were dominated by α-pinene emissions along with significant isoprene. BVOC measurements across different seasons (during 2009–2011) at a tropical forest site in French Guiana (Guyaflux site) revealed the dominance of isoprene emissions during all seasons. Irrespective of the type of the forest ecosystem, α-pinene was among the dominant monoterpenes emitted from all nine forests.